The yurt and world view features of the Kazakhs - A, Egyzbaeva M.; A, Мeirmanova G. (Farabi Journal of Social Sciences, 2019)
Abstract. Kazakh yurt is a traditional dwelling, existing since the ancient times and used up to the present time. The yurt of the Kazakhs is a portable house, which is typical for the inhabitants of the Great Steppe. This unique type of dwelling, made of felt and flexible willow rod, has become a symbol of the Motherland and its ancient culture. The main goal is to show the role of the yurt and its place in the worldview perception of the Kazakhs, as well as to introduce the semantic meaning of its details and parts. The article examines the details of the yurt as an ethnographic source in the studies of the traditional worldview of the Kazakhs. The article concerns not only a physical description of the yurt, but also conveys its semantic meaning. The symbol is considered as a sign characterizing its special significance. As a result, the authors came to the conclusion that the yurt has a complex architectural features and semantic meaning which reflects the level of cultural development of the Turkic-Mongolian tribes and their complex ideology. Thus, the symbolism of the yurt in the traditional worldview of the Kazakhs has also determined the experience of everyday life in their traditional perception of the world.